Antibacterial material and preparation method thereof
An antibacterial material using nano silver, zinc oxide, and diatomaceous earth on polylactic acid nanofibers addresses inefficiencies in air purification by enhancing dispersibility and photocatalytic efficiency, offering effective and sustainable air filtration.
Patent Information
- Application Number
- CN202310007391.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-04
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-01-04
AI Technical Summary
Existing methods are inefficient and environmentally unfriendly for removing bacteria from the air.
An antibacterial material composed of nano silver, zinc oxide, and diatomaceous earth, optionally loaded on polylactic acid nanofibers, utilizing electrospinning to create a fiber mesh with enhanced dispersibility and active sites for photocatalytic and bactericidal effects.
The material effectively removes bacteria from the air with improved mechanical properties, extended service life, and environmental sustainability due to biodegradability of polylactic acid.
Smart Images

Figure CN115928253B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of air purification, and in particular to an antibacterial material and a preparation method thereof. Background Art
[0002] Poor air quality threatens people's health, and air quality is becoming more and more a focus of attention.
[0003] However, it is currently difficult to remove bacteria in the air in an environmentally friendly and efficient manner. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention proposes an antibacterial material and a preparation method thereof, aiming to solve the problem that bacteria in the air are difficult to be removed in an environmentally friendly and efficient manner.
[0005] To achieve the above object, the present invention provides an antibacterial material, comprising: nano silver, zinc oxide, diatomaceous earth and polylactic acid, wherein the polylactic acid is a nanofiber structure.
[0006] Optionally, the nanosilver is loaded on the zinc oxide; and / or, the zinc oxide is loaded on the diatomaceous earth; and / or, the diatomaceous earth is loaded on the nanofiber structure of the polylactic acid.
[0007] Optionally, the molar ratio of the nano silver to the zinc oxide is (0.05-10):100.
[0008] Optionally, the mass of the diatomaceous earth is a, the sum of the masses of the nano-silver and the corresponding zinc oxide is b, and a:b=1:(10~0.5).
[0009] Optionally, the sum of the amounts of the nanosilver, the zinc oxide and the diatomaceous earth is c, the amount of the polylactic acid is d, and c:d=(0.5-10):100.
[0010] In order to achieve the above-mentioned purpose, the present invention also proposes a method for preparing the above-mentioned antibacterial material, comprising the following steps: S10, mixing nanosilver, zinc oxide, and diatomaceous earth, and adding a first organic solvent to obtain a suspension of nanosilver / zinc oxide / diatomaceous earth composite material; S20, mixing polylactic acid and a second organic solvent to obtain a polylactic acid solution; S30, adding the polylactic acid solution to the suspension of the nanosilver / zinc oxide / diatomaceous earth composite material and stirring to obtain a mixed solution, and then using an electrospinning method to prepare the mixed solution into an antibacterial material.
[0011] Optionally, step S10 includes: S1, mixing nano-silver and zinc oxide and stirring to obtain silver-loaded zinc oxide; S2, mixing the silver-loaded zinc oxide and diatomaceous earth, stirring, centrifuging, drying and grinding to obtain diatomaceous earth loaded with silver-loaded zinc oxide; S3, adding a first organic solvent to the diatomaceous earth loaded with silver-loaded zinc oxide to obtain a suspension of nano-silver / zinc oxide / diatomaceous earth composite material.
[0012] Optionally, in step S10, the first organic solvent includes at least one of chloroform, dichloromethane, and N,N-dimethylformamide; and / or, in step S20, the second organic solvent includes at least one of chloroform, dichloromethane, and N,N-dimethylformamide.
[0013] Optionally, in step S20, the mass ratio of the polylactic acid to the second organic solvent is 1:(5-10).
[0014] Optionally, in step S30, the humidity of the electrospinning method is 10%-40%; and / or, the voltage of the electrospinning method is 16kV-20kV; and / or, the injection rate of the electrospinning method is 0.5-1ml / h.
[0015] Beneficial effects of the present invention: The antibacterial material provided by the present invention is prepared by using diatomaceous earth loaded with zinc oxide and nano-silver composite particles, which overcomes the problem of easy agglomeration of nanoparticles. At the same time, diatomaceous earth loaded with silver-loaded zinc oxide can extend the service life of the antibacterial material and reduce the loss of antibacterial particles. In addition, the mechanical properties of the polylactic acid fiber mesh with added composite particles are improved, which can meet the needs of air filtration. The structure of the antibacterial material is a fiber mesh material, which is fully in contact with the air during the air purification process and exhibits excellent antibacterial properties. Since polylactic acid is an artificially synthesized bio-based material, it can be completely degraded after use, is environmentally friendly, and has the potential for sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 This is a scanning electron microscope image of a nano-silver / zinc oxide / diatomaceous earth composite material prepared in a specific embodiment of the present invention.
[0018] Figure 2 This is a scanning electron microscope image of an antibacterial material prepared in a specific embodiment of the present invention.
[0019] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0021] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.
[0022] At present, poor air quality threatens people's health, and air quality has become a focus of more and more people's attention. However, it is difficult to remove bacteria in the air in an environmentally friendly and efficient way.
[0023] In order to solve the above problems, the present invention provides an antibacterial material, comprising: nano silver, zinc oxide, diatomaceous earth and polylactic acid, wherein the polylactic acid is a nanofiber structure.
[0024] In a specific embodiment of the present invention, nanopores are distributed on the polylactic acid nanofibers and the surface of the nanofibers is inlaid with a composite material of nanosilver, zinc oxide, and diatomaceous earth. On the one hand, the polylactic acid material itself has certain antibacterial properties, and can play a synergistic role with the composite material of nanosilver / zinc oxide / diatomaceous earth, so that the antibacterial material has good adsorption and filtration effects and improves the antibacterial rate.
[0025] Furthermore, nanosilver is loaded on zinc oxide, zinc oxide is loaded on diatomaceous earth, and diatomaceous earth is loaded on the nanofiber structure of polylactic acid, so that the antibacterial material has good dispersibility and abundant active sites.
[0026] Furthermore, the molar ratio of the nano silver to the zinc oxide is (0.05-10): 100. The electrons in zinc oxide can be excited to form free electrons (e-) to realize the transition of electrons, thereby forming positively charged holes (h+), which can activate oxygen to become active oxygen [O], and can react with a variety of microorganisms to produce an oxidation reaction and thus play a bactericidal role; zinc oxide is a nanoparticle with piezoelectric properties. During the air purification process, the flow of air will exert pressure on zinc oxide, and the deformation of zinc oxide will form a piezoelectric effect, thereby promoting the directional migration of photoinduced electrons and holes and enhancing the photocatalytic efficiency. Similarly, it can also play an oxidative elimination role for some organic volatiles in the air. Nano silver has very good antibacterial properties. Under light, nano silver will produce a plasma resonance effect, thereby generating electrons. In silver-loaded zinc oxide, electrons are transferred from nano silver to nano zinc oxide, and compounding is carried out within the above-mentioned molar ratio range, which can improve the photocatalytic efficiency.
[0027] Furthermore, the mass of the diatomite is a, the sum of the mass of the nanosilver and the corresponding zinc oxide is b, and a:b=1:(10~0.5). The preparation of diatomite-loaded zinc oxide and nanosilver composite particles overcomes the problem of limited specific surface area of nanoparticles. Diatomite can load zinc oxide and nanosilver composite particles (silver-loaded zinc oxide) within the above-mentioned molar ratio range, which can extend the service life of the antibacterial material and reduce the loss of the antibacterial material.
[0028] Furthermore, the sum of the amounts of the nano-silver, the zinc oxide and the diatomaceous earth is c, the amount of the polylactic acid is d, and c:d=(0.5-10):100.
[0029] Since the semi-crystallization period of polylactic acid is too long, the crystallinity of polylactic acid can be improved by adding a nucleating agent, thereby changing the processability of polylactic acid. Therefore, diatomaceous earth loaded with silver-loaded zinc oxide is compounded with polylactic acid in the above ratio, and diatomaceous earth is used as a nucleating agent to enhance the mechanical properties of the antibacterial material and expand the application range of polylactic acid.
[0030] To solve the above problems, the present invention also provides a method for preparing an antibacterial material, comprising the following steps: S10, mixing nano silver, zinc oxide, and diatomaceous earth, and adding a first organic solvent to obtain a suspension of a nano silver / zinc oxide / diatomaceous earth composite material;
[0031] In a specific embodiment of the present invention, the first organic solvent is chloroform. Specifically, a certain amount of nanosilver / zinc oxide / diatomaceous earth composite material and chloroform are added to a beaker, stirred for 1-3 h to obtain a suspension of the nanosilver / zinc oxide / diatomaceous earth composite material, and ultrasonicated for 30 min-60 min to disperse the nanosilver / zinc oxide / diatomaceous earth composite material.
[0032] S20, mixing polylactic acid and a second organic solvent to obtain a polylactic acid solution;
[0033] In a specific embodiment of the present invention, the second organic solvent is chloroform, and a certain amount of polylactic acid is dissolved in chloroform, and stirred for 3-6 hours using magnetic stirring to obtain a polylactic acid solution.
[0034] S30, adding the polylactic acid solution to the suspension of the nanosilver / zinc oxide / diatomaceous earth composite material and stirring to obtain a mixed solution, and then using an electrospinning method to prepare the mixed solution into an antibacterial material.
[0035] In a specific embodiment of the present invention, a polylactic acid solution is added dropwise to a suspension of a nanosilver / zinc oxide / diatomaceous earth composite material, ultrasonicated for 30 min, and stirred for 10 h to fully disperse the nanosilver / zinc oxide / diatomaceous earth composite material in the polylactic acid solution. An electrospinning method is used to control the humidity range, voltage, feed rate, roller speed, and working distance of the reaction to obtain the antibacterial material.
[0036] Further, step S10 includes: S1, mixing nano silver and zinc oxide and stirring to obtain silver-loaded zinc oxide; in a specific embodiment of the present invention, weighing 180 mg of AgNO3 and completely dissolving it in 1 L of deionized water, heating it to boiling. Then slowly adding 20 mL of 1% sodium citrate solution. Continuously heating the flask containing the above solution for 1.5 h, and keeping the solution boiling. During this period, it can be observed that the mixed solution changes from clear to turbid, from transparent to light yellow, brown, brown, and finally to turbid gray-green, to obtain nano silver colloid. By ultrasonic dispersion technology, a certain amount of nano zinc oxide is dispersed in diethylene glycol to obtain a stable nano zinc oxide colloid. Under the condition of constant temperature magnetic stirring, silver and zinc oxide with a molar ratio of 0.05%-10% are selected to obtain silver-loaded zinc oxide.
[0037] S2, mixing the silver-loaded zinc oxide and diatomaceous earth, centrifuging, drying and grinding to obtain diatomaceous earth loaded with silver-loaded zinc oxide;
[0038] In a specific embodiment of the present invention, a certain mass of diatomaceous earth is weighed, a certain volume of silver-loaded zinc oxide mixed colloid is pipetted and added to the diatomaceous earth, and magnetic stirring is performed to uniformly mix the mixture. After multiple centrifugal washings using ethanol and deionized water, the mixture is dried and ground in a 70° C. forced drying oven, and passed through a 100-mesh sieve to obtain a nano-silver / zinc oxide / diatomaceous earth composite material. In a specific embodiment of the present invention, in order to better play the role of diatomaceous earth, the diatomaceous earth is first hydrophobically modified, specifically, 10g of ground and sieved diatomaceous earth is dispersed in 80 mL of dry toluene solution. After sufficient dispersion, a hydrophobic modifier is added dropwise from one end of a three-necked flask to the diatomaceous earth / toluene mixture during constant temperature stirring and reflux. The hydrophobic modifier is APTES, PTES or γ-MPS, wherein APTES is γ-aminopropyltriethoxysilane, PTES is heptadecafluorodecyltriethoxysilane, γ-MPS is γ-methacryloxypropyltrimethoxysilane, and the mass ratio of the hydrophobic modifier to the diatomaceous earth is 1:2, and then the reflux temperature is controlled to be 75-85°C, the rotation speed is 300-500 rpm, and the mixture is stirred for 9-12 ℃. h, after the reaction is completed, the product is centrifuged and filtered, washed with ethanol for 3 times (to remove the solvent and excess unreacted silane coupling agent), and dried at 60-80°C for 8-12h to obtain hydrophobically modified diatomite. Since the hydroxyl groups on the surface of diatomite have strong hydrophilicity, hydrophobic modification of diatomite can improve the dispersion performance of diatomite.
[0039] S3, adding a first organic solvent to the diatomaceous earth loaded with silver-loaded zinc oxide to obtain a suspension of nano-silver / zinc oxide / diatomaceous earth composite material.
[0040] Further, in step S10, the first organic solvent includes at least one of chloroform, dichloromethane, and N,N-dimethylformamide; and / or, in step S20, the second organic solvent includes at least one of chloroform, dichloromethane, and N,N-dimethylformamide.
[0041] In a specific embodiment of the present invention, the first organic solvent is chloroform and N,N-dimethylformamide (volume ratio is 8:2), and the second organic solvent is chloroform and N,N-dimethylformamide (volume ratio is 8:2). The amount of the above solvents can make the suspension of the nanosilver / zinc oxide / diatomaceous earth composite material better dispersed into the polylactic acid solution, and can maximize the synergistic effect of the four materials including diatomaceous earth, activate the active sites, and improve the photocatalytic efficiency.
[0042] Furthermore, in step S20, the mass ratio of the polylactic acid to the second organic solvent is 1:(5-10). Mixing the components with the above parameters can make the polylactic acid solution reach the optimal concentration for compounding with the nanosilver / zinc oxide / diatomaceous earth composite material, and also lay a microscopic foundation for preparing polylactic acid fibers by electrospinning.
[0043] Further, in step S30, the humidity set in the electrospinning method is 10%-40%; and / or, the voltage set is 16kV-20kV; and / or, the injection rate is 0.5-1ml / h. When the humidity is high, water may be concentrated on the fiber surface during electrospinning, thereby affecting the fiber morphology; when the humidity is low, the volatile solvent may dry quickly, and the solvent volatilization rate may be faster than the speed at which it moves out of the needle, resulting in needle blockage, so that the electrospinning process can only last for a very short time. The magnitude of the voltage matches the mechanical relationship between the electric field force of the jet and the viscosity stress of the solution, and affects the result of electrospinning together with the injection rate and humidity. In one embodiment of the present invention, the humidity set in the electrospinning method is 10%-40%, the voltage set is 16kV-20kV, the injection rate is 0.5-1ml / h, the roller speed is 200-1000r / min, and the working distance is 10-20cm, and an antibacterial material is prepared.
[0044] The experimental materials used in the embodiments of the present invention include:
[0045]
[0046] Example 1: Preparation of antibacterial material
[0047] Preparation of silver-loaded zinc oxide: Weigh 180 mg of AgNO3 and completely dissolve it in 1 L of deionized water, and heat it to boiling. Then slowly add 20 mL of 1% sodium citrate solution into the flask containing the above solution, continue heating for 1.5 h, and keep boiling. When the mixed solution turns turbid gray-green, nanosilver colloid is obtained. By ultrasonic dispersion technology, a certain amount of nanozinc oxide is dispersed in diethylene glycol to obtain a stable nanozinc oxide colloid. Under constant temperature magnetic stirring, select a molar ratio of 0.05% silver and zinc oxide to obtain silver-loaded zinc oxide.
[0048] Hydrophobic modification of diatomite: Disperse 10 g of ground and sieved diatomite in 80 mL of dry toluene solution. After sufficient dispersion, add hydrophobic modifier APTES from one end of a three-necked flask to the diatomite / toluene mixture under constant temperature stirring and reflux, wherein the mass ratio of hydrophobic modifier to diatomite is 1:2. Stir the mixture at 80°C (300 rpm) and reflux for 12 h. After the silanization reaction, centrifuge and filter the product, wash it with ethanol three times (to remove the solvent and excess unreacted silane coupling agent), and dry it at 60-80°C for 8-12 h to obtain hydrophobically modified diatomite.
[0049] Preparation of nanosilver / zinc oxide / diatomite composite material: Weigh 0.0075g of hydrophobically modified diatomite, pipette 75mL of silver-loaded zinc oxide mixed colloid into the diatomite, stir evenly with magnetic force, wash by centrifugation several times with ethanol and deionized water, dry and grind in a 70℃ forced air drying oven, and pass through a 100 mesh sieve to obtain nanosilver / zinc oxide / diatomite composite material. Divide 75ml of Ag / zinc oxide mixed colloid into 5 times, and repeat the above experimental process to increase the thickness of the load.
[0050] Preparation of antibacterial materials: Add a certain amount of nanosilver / zinc oxide / diatomite composite material and chloroform in a beaker, stir for 1 h to make a suspension of nanosilver / zinc oxide / diatomite composite material, and ultrasonicate for 30 min to disperse the nanosilver / zinc oxide / diatomite composite material. Secondly, dissolve 1.5 g of polylactic acid in chloroform, the mass ratio of polylactic acid to chloroform is 1:10 (the volume ratio of chloroform used as solvent twice is 8:2), use magnetic stirring, stir for 3 h, and mix evenly. Then add the polylactic acid solution dropwise to the suspension of nanosilver / zinc oxide / diatomite composite material, ultrasonicate for 30 min, stir for 10 h, so that the nanosilver / zinc oxide / diatomite composite material is fully dispersed in the polylactic acid solution. Among them, the mass ratio of nanosilver / zinc oxide / diatomaceous earth composite material to polylactic acid solution was 0.5%. Using electrospinning method, within the humidity range of 20%, the voltage was set to 18 kV, the feed rate was 1 mL / h, the roller speed was 300 r / min, and the working distance was 15 cm to obtain the antibacterial material, sample it, and name it Ag / ZnO / DE@PLA-1.
[0051] Example 2: Preparation of antibacterial material
[0052] Preparation of silver-loaded zinc oxide: Weigh 180 mg of AgNO3 and completely dissolve it in 1 L of deionized water, and heat it to boiling. Then slowly add 20 mL of 1% sodium citrate solution into the flask containing the above solution, continue heating for 1.5 h, and keep boiling. When the mixed solution turns turbid gray-green, nanosilver colloid is obtained. By ultrasonic dispersion technology, a certain amount of nanozinc oxide is dispersed in diethylene glycol to obtain a stable nanozinc oxide colloid. Under constant temperature magnetic stirring, select a molar ratio of 0.05% silver and zinc oxide to obtain silver-loaded zinc oxide.
[0053] Hydrophobic modification of diatomite: Disperse 10 g of ground and sieved diatomite in 80 mL of dry toluene solution. After sufficient dispersion, add hydrophobic modifier APTES from one end of a three-necked flask to the diatomite / toluene mixture under constant temperature stirring and reflux, wherein the mass ratio of hydrophobic modifier to diatomite is 1:2. Stir the mixture at 80°C (300 rpm) and reflux for 12 h. After the silanization reaction, centrifuge and filter the product, wash it with ethanol three times (to remove the solvent and excess unreacted silane coupling agent), and dry it at 60-80°C for 8-12 h to obtain hydrophobically modified diatomite.
[0054] Preparation of nanosilver / zinc oxide / diatomite composite material: Weigh 0.0075g of hydrophobically modified diatomite, pipette 75mL of silver-loaded zinc oxide mixed colloid into the diatomite, stir evenly with magnetic force, wash by centrifugation several times with ethanol and deionized water, dry and grind in a 70℃ forced air drying oven, and pass through a 100 mesh sieve to obtain nanosilver / zinc oxide / diatomite composite material. Divide 75ml of Ag / zinc oxide mixed colloid into 5 times, and repeat the above experimental process to increase the thickness of the load.
[0055] Preparation of antibacterial materials: Add a certain amount of nanosilver / zinc oxide / diatomite composite material and chloroform in a beaker, stir for 1 h to make a suspension of nanosilver / zinc oxide / diatomite composite material, and ultrasonicate for 30 min to disperse the nanosilver / zinc oxide / diatomite composite material. Secondly, dissolve 1.5 g of polylactic acid in chloroform, the mass ratio of polylactic acid to chloroform is 1:5 (the volume ratio of chloroform used as solvent twice is 8:2), use magnetic stirring, stir for 3 h, and mix evenly. Then add the polylactic acid solution dropwise to the suspension of nanosilver / zinc oxide / diatomite composite material, ultrasonicate for 30 min, stir for 10 h, so that the nanosilver / zinc oxide / diatomite composite material is fully dispersed in the polylactic acid solution. Among them, the mass ratio of nanosilver / zinc oxide / diatomaceous earth composite material to polylactic acid solution was 0.5%. Using electrospinning method, within the humidity range of 20%, the voltage was set to 18 kV, the feed rate was 1 mL / h, the roller speed was 300 r / min, and the working distance was 15 cm to obtain the antibacterial material, sample it, and name it Ag / ZnO / DE@PLA-2.
[0056] Example 3: Preparation of antibacterial material
[0057] Preparation of silver-loaded zinc oxide: Weigh 180 mg of AgNO3 and completely dissolve it in 1 L of deionized water, and heat it to boiling. Then slowly add 20 m sodium citrate solution with a concentration of 1% into the flask containing the above solution, continue heating for 1.5 h, and keep boiling. When the mixed solution turns turbid gray-green, nanosilver colloid is obtained. By ultrasonic dispersion technology, a certain amount of nanozinc oxide is dispersed in diethylene glycol to obtain a stable nanozinc oxide colloid. Under the condition of constant temperature magnetic stirring, select silver and zinc oxide with a molar ratio of 0.05% to obtain silver-loaded zinc oxide.
[0058] Hydrophobic modification of diatomite: Disperse 10 g of ground and sieved diatomite in 80 mL of dry toluene solution. After sufficient dispersion, add hydrophobic modifier APTES from one end of a three-necked flask to the diatomite / toluene mixture under constant temperature stirring and reflux, wherein the mass ratio of hydrophobic modifier to diatomite is 1:2. Stir the mixture at 80°C (300 rpm) and reflux for 12 h. After the silanization reaction, centrifuge and filter the product, wash it with ethanol three times (to remove the solvent and excess unreacted silane coupling agent), and dry it at 60-80°C for 8-12 h to obtain hydrophobically modified diatomite.
[0059] Preparation of nano-silver / zinc oxide / diatomaceous earth composite materials: weigh a certain mass of diatomaceous earth, pipette a certain volume of silver-loaded zinc oxide mixed colloid into the diatomaceous earth, the mass ratio of diatomaceous earth to silver-loaded zinc oxide is 1:10, stir evenly with a magnetic stirrer, wash by centrifugation multiple times with ethanol and deionized water, dry and grind in a 70°C forced air drying oven, and pass through a 100-mesh sieve to obtain a nano-silver / zinc oxide / diatomaceous earth composite material.
[0060] Preparation of antibacterial materials: Add a certain amount of nanosilver / zinc oxide / diatomite composite material and chloroform in a beaker, stir for 3 hours to make a suspension of nanosilver / zinc oxide / diatomite composite material, and ultrasonicate for 60 minutes to disperse the nanosilver / zinc oxide / diatomite composite material. Secondly, a certain amount of polylactic acid was dissolved in chloroform, the mass ratio of polylactic acid to chloroform was 1:10 (the volume ratio of chloroform used as solvent twice was 8:2), and magnetic stirring was used to stir for 6 hours to mix evenly. Then the polylactic acid solution was added dropwise to the suspension of nanosilver / zinc oxide / diatomite composite material, ultrasonicated for 30 minutes, and stirred for 10 hours to fully disperse the nanosilver / zinc oxide / diatomite composite material in the polylactic acid solution. Among them, the mass ratio of nanosilver / zinc oxide / diatomaceous earth composite material to polylactic acid solution was 0.5%. Using electrospinning method, within the humidity range of 40%, the voltage was set to 20 kV, the feed rate was 1 mL / h, the roller speed was 1000 r / min, and the working distance was 20 cm to obtain the antibacterial material, sample it, and name it Ag / ZnO / DE@PLA-3.
[0061] Example 4: Preparation of antibacterial material
[0062] Preparation of silver-loaded zinc oxide: Weigh 180 mg of AgNO3 and completely dissolve it in 1 L of deionized water, and heat it to boiling. Then slowly add 20 m of 1% sodium citrate solution into the flask containing the above solution, continue heating for 1.5 h, and keep boiling. When the mixed solution turns turbid gray-green, nanosilver colloid is obtained. By ultrasonic dispersion technology, a certain amount of nanozinc oxide is dispersed in diethylene glycol to obtain a stable nanozinc oxide colloid. Under constant temperature magnetic stirring, select a molar ratio of 10% silver and zinc oxide to obtain silver-loaded zinc oxide.
[0063] Hydrophobic modification of diatomite: Disperse 10 g of ground and sieved diatomite in 80 mL of dry toluene solution. After sufficient dispersion, add hydrophobic modifier γ-MPS from one end of a three-necked flask to the diatomite / toluene mixture under constant temperature stirring and reflux, wherein the mass ratio of hydrophobic modifier to diatomite is 1:2. Stir the mixture at 80°C (500 rpm) and reflux for 12 h. After the silanization reaction, centrifuge and filter the product, wash it three times with ethanol (to remove the solvent and excess unreacted silane coupling agent), and dry it at 60-80°C for 8-12 h to obtain hydrophobically modified diatomite.
[0064] Preparation of nano silver / zinc oxide / diatomaceous earth composite materials: weigh a certain mass of diatomaceous earth, pipette a certain volume of silver-loaded zinc oxide mixed colloid into the diatomaceous earth, the mass ratio of diatomaceous earth to silver-loaded zinc oxide is 1:0.5, stir evenly with a magnetic stirrer, wash by centrifugation multiple times with ethanol and deionized water, dry and grind in a 70°C forced air drying oven, and pass through a 100-mesh sieve to obtain a nano silver / zinc oxide / diatomaceous earth composite material.
[0065] Preparation of antibacterial materials: Add a certain amount of nanosilver / zinc oxide / diatomite composite material and chloroform in a beaker, stir for 1 hour to make a suspension of nanosilver / zinc oxide / diatomite composite material, and ultrasonicate for 30 minutes to disperse the nanosilver / zinc oxide / diatomite composite material. Secondly, a certain amount of polylactic acid was dissolved in chloroform, the mass ratio of polylactic acid to chloroform was 1:10 (the volume ratio of chloroform used as solvent twice was 8:1), and magnetic stirring was used to stir for 3 hours to mix evenly. Then the polylactic acid solution was added dropwise to the suspension of nanosilver / zinc oxide / diatomite composite material, ultrasonicated for 30 minutes, and stirred for 10 hours to fully disperse the nanosilver / zinc oxide / diatomite composite material in the polylactic acid solution. Among them, the mass ratio of nanosilver / zinc oxide / diatomaceous earth composite material to polylactic acid solution was 10%. Using electrospinning method, within the humidity range of 10%, the voltage was set to 16 kV, the feed rate was 0.5 ml / h, the roller speed was 200 r / min, and the working distance was 10 cm to obtain the antibacterial material, sample it, and name it Ag / ZnO / DE@PLA-4.
[0066] Comparative Example 1: Preparation of polylactic acid fiber
[0067] Weigh 1.5 g of polylactic acid and dissolve it in 10 mL of organic solvent (v chloroform: v N, N-dimethylformamide = 8:2), use magnetic stirring, stir for 3 hours, and obtain a uniformly mixed polylactic acid solution. Using the electrospinning method, under 20% humidity conditions, set the voltage to 18 kV, the sample rate to 1 ml / h, the roller speed to 300 r / min, and the working distance to 15 cm, obtain polylactic acid electrospinning for antibacterial performance testing, take samples, and name the samples as PLA.
[0068] Comparative Example 2: Preparation of Nanosilver / Polylactic Acid Composite Fiber
[0069] Weigh 180 mg of AgNO3 and completely dissolve it in 1 L of deionized water, and heat it to boiling. Then slowly add 20 mL of 1% sodium citrate solution. Continue heating the flask with the above solution for 1.5 h and keep it boiling. During this period, it can be observed that the mixed solution changes from clear to turbid, from transparent to light yellow, brown, brown, and finally to turbid gray-green, becoming nanosilver colloid.
[0070] Then, 4 mL of homemade nanosilver colloid was taken, washed by centrifugation with ethanol and deionized water several times, and placed in an oven at 60 ° C. After 10 hours, an appropriate amount of chloroform was added, stirred for 1 hour to make a suspension of nanosilver, and ultrasonicated for 30 minutes to disperse the Ag particles. Secondly, 1.5 g of polylactic acid was dissolved in an organic solvent, and magnetic stirring was used for stirring for 3 hours to dissolve the polylactic acid and mix evenly. Then the polylactic acid solution was added dropwise to the suspension of nanosilver particles, ultrasonicated for 30 minutes, and stirred for 10 hours to fully disperse the nanosilver particles in the polylactic acid solution to obtain a polylactic acid mixed solution containing nanosilver particles. Using the electrospinning method, under 20% humidity conditions, the voltage was set to 18kV, the feed rate was 1ml / h, the roller speed was 300r / min, and the working distance was 15cm, and the nanosilver / polylactic acid composite fiber was obtained, and the sample was taken, and the sample was named Ag@PLA.
[0071] Comparative Example 3: Preparation of zinc oxide / polylactic acid composite fiber
[0072] Take 0.0075 g zinc oxide and add an appropriate amount of chloroform, stir for 1 h to make a zinc oxide suspension, and ultrasonicate for 30 min to disperse the zinc oxide particles. Secondly, dissolve 1.5 g polylactic acid in an organic solvent, use magnetic stirring, stir for 3 h, add the polylactic acid solution dropwise to the suspension of zinc oxide particles, ultrasonicate for 30 min, and stir for 10 h to fully disperse the zinc oxide particles in the polylactic acid solution. Prepare a polylactic acid mixed solution containing zinc oxide particles, use electrospinning, under 20% humidity conditions, set the voltage to 18 kV, the feed rate to 1 ml / h, the roller rate to 300 r / min, and the working distance to 15 cm, obtain zinc oxide / polylactic acid composite fibers, take samples, and name the sample ZnO@PLA.
[0073] Comparative Example 4: Preparation of Nanosilver / Zinc Oxide / Polylactic Acid Composite Fiber
[0074] 203 mg of nano zinc oxide was ultrasonically dispersed in 100 mL of diethylene glycol solvent to form a stable nano zinc oxide colloid; then 125 mL of nano silver colloid in Example 1 was taken and mixed evenly with the nano zinc oxide colloid, and stirred at 90-100°C for 1.5 h using constant temperature magnetic stirring to obtain a nano composite material. After multiple centrifugal washings with ethanol and deionized water, the mixture was placed in an oven at 60°C for 10 h to obtain a powdered sample.
[0075] Take 0.0075g of the above-mentioned Ag / zinc oxide nanocomposite material, add an appropriate amount of chloroform, stir for 1 h to make a Ag / zinc oxide suspension, and ultrasonicate for 30 min to disperse the nanosilver / zinc oxide particles. Secondly, dissolve 1.5 g of polylactic acid in an organic solvent, use magnetic stirring, stir for 3h, the polylactic acid is dissolved, and mix evenly. Then add the polylactic acid solution dropwise to the suspension of nanosilver / zinc oxide particles, ultrasonicate for 30 min, stir for 10 h, and fully disperse the nanosilver / zinc oxide particles in the polylactic acid solution. Prepare a polylactic acid mixed solution containing Ag / zinc oxide particles.
[0076] Using the electrospinning method, under 20% humidity conditions, the voltage was set to 18 kV, the feed rate was 1 ml / h, the roller speed was 300 r / min, and the working distance was 15 cm to obtain nanosilver / zinc oxide / polylactic acid composite fibers, and the samples were taken and named Ag / ZnO@PLA.
[0077] Further, the antibacterial performance test experiment of Example 1 and Comparative Examples 1-4 was carried out, and the specific operation was as follows: dissolve the nutrient broth powder with distilled water, prepare the liquid culture medium, place the culture medium in a conical flask, sterilize under high temperature conditions, and cool it for standby. According to the aseptic operation method on the purification operation table, add Escherichia coli bacterial solution to the conical flask respectively, put it in a shaking table at 37 ° C and 220r / min for 3 h, and then add the polylactic acid fiber sample. The sample is a polylactic acid fiber membrane of uniform size and a nanofiber membrane of polylactic acid loaded composite particles. In the control group, no substance was added. The OD value of the bacterial solution within 24h was recorded, and the growth curve of Escherichia coli was drawn. After that, the bacterial solution at 24h was taken, diluted, and coated on the solid culture medium with a triangular coating rod, and cultured in a constant temperature incubator for 12 hours, and the bacterial colonies were counted and the antibacterial rate was calculated. The test results are summarized in Table 1.
[0078] Table 1. Treatment effect experiments of Example 1 and Comparative Examples 1-4
[0079]
[0080] Through the above treatment effect experiment, it can be intuitively shown that the antibacterial material provided by the present invention can overcome the problem of easy agglomeration of nanoparticles by using diatomite loaded zinc oxide and nano-silver composite particles. At the same time, diatomite loaded with silver-loaded zinc oxide can extend the service life of the antibacterial material and reduce the loss of antibacterial particles. In addition, the mechanical properties of the polylactic acid fiber net with added composite particles have been improved, which can meet the needs of air filtration. The structure of the antibacterial material is a fiber mesh material, which is fully in contact with air during the air purification process and shows excellent antibacterial properties. Since polylactic acid is a synthetic bio-based material, it can be completely degraded after use, is environmentally friendly, and has the potential for sustainable development.
[0081] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. An antibacterial material, characterized in that: include: Nano silver, zinc oxide, diatomaceous earth and polylactic acid, wherein the polylactic acid is a nanofiber structure; The nano silver is loaded on the zinc oxide; The zinc oxide is supported on the diatomaceous earth; The diatomaceous earth is loaded on the nanofiber structure of the polylactic acid; The preparation method of the antibacterial material comprises the following steps: S10, mixing nano silver, zinc oxide, and diatomaceous earth, and adding a first organic solvent to obtain a suspension of nano silver / zinc oxide / diatomaceous earth composite material; S20, mixing polylactic acid and a second organic solvent to obtain a polylactic acid solution; S30, adding the polylactic acid solution to the suspension of the nanosilver / zinc oxide / diatomaceous earth composite material and stirring to obtain a mixed solution, and then using an electrospinning method to prepare the mixed solution into an antibacterial material; The step S10 comprises the following steps: S1, mixing nano silver and zinc oxide and stirring to obtain silver-loaded zinc oxide; S2, mixing the silver-loaded zinc oxide and diatomaceous earth, centrifuging, drying and grinding to obtain diatomaceous earth loaded with silver-loaded zinc oxide; S3, adding a first organic solvent to the diatomaceous earth loaded with silver-loaded zinc oxide to obtain a suspension of nano-silver / zinc oxide / diatomaceous earth composite material; The molar ratio of the nano silver to the zinc oxide is (0.05-10):
100.
2. The antibacterial material according to claim 1, characterized in that: The mass of the diatomaceous earth is a, the sum of the masses of the nano-silver and the corresponding zinc oxide is b, and a:b=1:(10~0.5).
3. The antibacterial material according to claim 1, characterized in that: The sum of the amounts of the nano-silver, the zinc oxide and the diatomaceous earth is c, the amount of the polylactic acid is d, and c:d=(0.5-10):
100.
4. The antibacterial material according to claim 1, characterized in that: In step S10, The first organic solvent includes at least one of chloroform and N,N-dimethylformamide; In step S20, the second organic solvent includes at least one of chloroform and N,N-dimethylformamide.
5. The antibacterial material according to claim 1, characterized in that: In step S20, the mass ratio of the polylactic acid to the second organic solvent is 1:(5-10).
6. The antibacterial material according to claim 1, characterized in that: In step S30, the humidity of the electrospinning method is 10%-40%; The voltage of the electrospinning method is 16kV-20kV; The injection rate of the electrospinning method is 0.5-1 ml / h.
Citation Information
Patent Citations
High-transparency and low-cost polylactic acid composite material and preparation method thereof
CN107312295A
Preparation method for Ag@ZnO@JPLA / beta-CD composite nano-fiber membrane
CN110042567A
Hydrophobic modified diatom shell material, preparation method and application thereof, and hydrophobic assembly containing hydrophobic modified diatom shell material
CN111704822A
Degradable mask and preparation method thereof
CN114045610A